Analysis of Problem Solving Skills in the Vocational High School Using Direct Current Electricity as A Case Study - Riska Dwi Anggraini; Tjipto Prastowo; Elok Sudibyo (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2022)
This study examines problem-solving as one of fundamental cognitive processes required for the 21st century skills. In this context, physics learning is generally directed to focusing on how students in schools attain this ability, which includes analyzing, evaluating, and reflecting activities to find solutions to a problem based on student’s own knowledge and experience. The aim of the current study is to determine student’s profiles on problem-solving skills at the initial stage for a given subject of electric circuits in a classroom setting. Students of Muhammadiyah 3 Vocational High School, Gresik, Indonesia specialized in electrical engineering were sampled as targetted people. The method used was a descriptive approach, where instruments for data collection were developed using Polya's steps. Research findings were derived from student performance indicators, namely understanding a given problem which scored 55.9%, planning strategy for a solution to the problem which achieved 48.7%, implementing the strategy which obtained 7.7%, and checking the solution which marked 13.85%. In conclusion, the results showed that students’ skills on problem-solving was found to be at a very low level.